Quality analysis of meats using FTIR spectroscopy, colour spectrophotometer, texture analyser and physical image analysis - Abd Rashid, Ainur Nalisa; Kormin, Faridah; Asman, Saliza (Penerbit UMT, 2021)
Assessment methods of meat such as physicochemical analyses and microbial techniques are laborious and time-consuming. A rapid and non-destructive quality analysis method of meat is needed and important to satisfy consumer demand. This study aims to implement FT-IR spectroscopy, colour spectrophotometer, texture analyser and physical image analysis to analyse the quality of raw, boiling and roasting meat. The FT-IR analysis revealed the functional group for proteins, triglycerides, fatty acids and carbohydrates with different intensities mostly focused at 3300 cm-1, 2967 cm-1, 1639 cm-1, 1546 cm-1, 1453 cm-1. Colour parameters showed slight alterations and partial degradation of some proteins in meat was observed. L*, a* and b* for raw meats decreased, L* and b* for boiled and roasted meats increased, and a* decreased. The texture analysis shows significant different tenderness of meats and even cooking methods. Tenderness of raw meats decreased while the cooked meats increased from the first until the fifth day. The image analysis shows no significant changes in the meat textural surface. The findings show that the quality of cooked meats was better than raw meats. The assessment methods applied can evaluate the quality of meats and provide additional information on the physical changes of meat composition and structure.